A escola da juventude paulista a expansão dos ginásios públicos e o campo político no Estado de São Paulo (1947-1963) - Diniz, Carlos Alberto (Editora Oficina Universitária, 2020)
How did the expansion of public gymnasiums occur in the State of São Paulo during the redemocratization period? How did the Executive and State Legislative Powers act on this issue to respond to the demands of the population of the capital and other municipalities in São Paulo? These questions guided this entire work, the results of which indicate a notorious process of expansion of junior high schools at an extraordinarily fast pace, which occurred in a discrepant way in several aspects, since political criteria prevailed to the detriment of educational criteria. A very topical topic of interest to students, teachers and researchers in the area of Education, the issue of expanding educational networks directly concerns the democratization and expansion of citizenship. In this sense, knowledge of a historical nature, especially regarding the relationship between politics and education, can greatly contribute to qualify the discussion and support reflections on the expansion of schooling in the country and, likewise, problematize the current Brazilian educational situation.